Strategic shifts: How studio teachers use direction and support to build learner agency in the figured world of visual art. Issue 1 (1st January 2022) - Sheridan, Kimberly M.; Zhang, Xiaorong; Konopasky, Abigail W.
ABSTRACT: Background: In studio art, students are expected to be highly agentive—to engage in creative processes to form personalized representations of ideas, yet we lack knowledge on how teachers support their agency. Approaching agency as co-constructed practices across temporal dimensions, we examine how teachers shift between autonomy-supportive and directive approaches, building students' artistic agency. Methods: Secondary qualitative analysis of video-recordings (49 hours) of four teachers' studio art classes in two arts-intensive high schools used observational frameworks on autonomy-support, theoretical constructs of spaces of authoring and temporal orientations to agency, and functional linguistic agency markers. Findings: Studio teaching is primarily autonomy-supportive, but teachers strategically shift their enacted and linguistic practices to directive approaches, such as commands and constraints, taking control over parts of the creative process to build students' artistic agency. Contribution: Our work on teachers co-constructing artistic agency with students adds nuance to accounts of how teachers support agency, particularly forms of direction on open-ended problems. Our theoretical lens of the temporal process of agency and methodological approach of attending to enacted and linguistic practices and to when teachers shift to and away from directiveness, could be used in other learning settings to examine how agency is co-constructed.